Factors Affecting the Perceptions of Small-Scale Organic Farmers in South Africa: An OLS Approach - Eyinade, Gabriel Adewunmi; Akharume, Celestine Ohi (Journal of Economics and Behavioral Studies, 2018)
Much investments have been tailored towards organic farming by several stakeholders in recent years. Reasons for these are poverty mitigation, income generation as well as food security and good dietary diets. Unfortunately, there are no significant improvements in those areas where organic farming has been funded and encouraged. The study aims at identifying factors affecting the perceptions of small-scale organic farmers using ordinary least square regression model (OLS). One hundred and sixty structure questionnaires were administered on 160 small-scale organic farmers in Amathole District Municipality to gather data for the study. The results revealed that gender and educational level are the major factors affecting the perceptions of small-scale organic farmers in South Africa. Nevertheless, to open the prospective of smallscale organic farmers, the study suggested that these farmers should have greater access to extension services and support. This will go a long way in assisting the farmers to diversify and improve their production, thus enhancing livelihoods and creating markets for organic foods.